Improvement of in vitro regeneration frequency, polyphenolic and antioxidant profile of Strawberry (Fragaria ananassa Cv. Chandler) via indirect organogenesis - Rukh, Shah; Kazmi, Abeer; Nabi, Ghulam; Irshad, Muhammad; Ali, Amir; Muhammad, Sher; Mashwani, Zia-ur-Rehman; Sultana, Tahira (Journal of Pure and Applied Agriculture, 2023)
The Strawberry (Fragaria ananassa) is a fleshy fruit crop from the Rosacea family, considered one of the most economically significant plants. Strawberry is an accessory fruit crop that has become known for its attractive red color, sweet scent and taste, and high fiber, nutrient, and sugar content. Strawberry contains a significant portion of phenolic, flavonoids, Vitamin C, and potent antioxidants. To use in vitro approaches in berry crops, efficient regeneration protocols must be established. The main intent of the current study was to establish an effectual regenerative protocol and evaluate the regeneration efficacy of Thidiazuron (TDZ) and the antioxidant profile of Ex-vitro and in vitro strawberry plants. In vitro-derived stem explants were inoculated on Murashige and Skoog (MS) media augmented with diverse Plant growth regulators (PGRs) for initiation of callus. The induced calli were further subcultured on MS media containing different concentrations of TDZ for shoot stimulation. In vitro-derived shoots were further shifted to the rooting medium. The Polyphenolic content was determined for regenerated ex-vitro and in vitro plants. MS media comprising NAA (0.5mg/L) + 2, 4-D (0.5mg/L) induced the highest callus formation. MS media added with TDZ (1.5 mg/L) significantly enhanced induction of shoots, maximum shooting frequency, and highest shoot numbers from callus. MS half-strength media with IBA (1mg/L) exhibited early rooting, maximum rooting response, and the highest number of roots. Polyphenols and antioxidant activity in in vitro plants were considerably better than in ex-vitro plants. Exogenous supplementation of MS solid media with 2,4-D and NAA was the most effective treatment to induce callogenesis, while TDZ was effective for early initiation of shoot formation from callus. The existing protocol has led to increased acclimation and survival of regenerated plantlets with increased polyphenolic quantity and antioxidant activity.